1992
DOI: 10.1111/j.1365-2044.1992.tb02337.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing epidural catheter migration

Abstract: SummaryThe incidence and amount of migration of epidural catheters was investigated in a prospective randomised study of 153 women who required analgesia in labour. Inward or outward migration occurred in 36% of patients. Inward migration by 1-3 cm occurred in 21 (13.7%) patients and outward migration by I cm or more occurred in 34 (22.2%); three (2%) catheters migrated out rhrough the skin. There were SigniJicant positive correlations between outward migration and weight, body mass index, and depth of the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
5

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 8 publications
(3 reference statements)
2
34
0
5
Order By: Relevance
“…In their study, out of the 60 migrated catheters only 17 catheters migrated inside by more than 1 cm. Similar findings were also observed by Bishton et al 6 Our study also showed similar results with no epidural catheter migrating inward. In our study, the incidence of migration was more in the Steri-Strips group as compared with the tunneling group.…”
Section: Discussionsupporting
confidence: 82%
“…In their study, out of the 60 migrated catheters only 17 catheters migrated inside by more than 1 cm. Similar findings were also observed by Bishton et al 6 Our study also showed similar results with no epidural catheter migrating inward. In our study, the incidence of migration was more in the Steri-Strips group as compared with the tunneling group.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is consistent with the result of the study by Bhiston et al who found that the epidural catheter has a tendency to migrate both further into and out of the epidural space after it has been secured. They found that 22% of the catheters migrated more than 1 cm out of the epidural space [13]. Current literature suggests that threading too much of the epidural catheter into the epidural space may direct the catheter right or left, rather than into the middle of the space.…”
Section: Discussionmentioning
confidence: 99%
“…When DepoDur is injected epidurally, the vesicles slowly erode and reorganize, allowing for the slow and consistent release of morphine to provide pain relief. The DepoFoam drug delivery system may circumvent several of the potential complications associated with indwelling catheters 5,[9][10][11][12][13][14] and may reduce the need for patient-controlled-analgesia pumps.…”
Section: Evaluation Of a Single-dose Extended-release Epidural Morphmentioning
confidence: 99%